Major Turns in Planned Development of Nepal - Srivastava, Nagendra Lal (Journal of Nepalese Business Studies, 2009)
Three major turns in the pattern of development plans have been clearly realized. First has been seen in fifth plan in which the concept of regional de velopment was introduced along with strengthening of party less Panchayat system. The Second turn has been found in eighth plan that was the first plan after the restoration of multi party system in 1990. The change in this plan was seen in the form of guaranteeing democratic rights and opportunities to the people in existing socio economic and political scenario along with the promotion of privatization and economic liberalization. The third turn has been reflected in the current interim plan. The change has been seen through the aspirations of people that have been incorporated here in various ways to make a new Nepal. All the turns have been identified through the difference in plan objectives, policies and strategies that have been affected by influential change in socio political situations of the country due to some epoch making events. Key words: Major turns, planned development The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 1-15